The Effect of Bilateral Eyestalk Ablation on Signal Transduction Pathways of Ion Regulation of Litopenaeus vannamei. Issue 1 (9th September 2016) - Li, Li; Pan, Luqing; Hu, Dongxu; Liu, Dong; Liu, Maoqi
Abstract: A study was performed on the effects of bilateral eyestalk ablation on signal transduction pathways of ion regulation of Litopenaeus vannamei . The study included three treatments (starvation group, bilateral eyestalk ablation, and starvation and bilateral eyestalk ablation) in addition to a control group. The shrimp were sampled at 0, 12, 24, and 48 h. Results showed that the ablation of bilateral eyestalk had significant effects on the contents of three kinds of biogenic amines (BAs), cyclic guanosine monophosphate (cGMP), and the activities of three kinds of ion‐transport enzymes ( P < 0.05). According to these results, bilateral eyestalk ablation had significant effects on the ion signal pathway of L. vannamei . The same changes were observed in 5‐hydroxytryptamine (5‐HT) contents, Na + ‐K + ‐ATPase, and HCO3 − ‐ATPase activities, suggesting that crustacean hyperglycemic hormone (CHH) regulated the changes in ion‐transport enzymes, mediated by BAs and cGMP. The specific pathways may be 5‐HT → cGMP → Na + ‐K + ‐ATPase, HCO3 − ‐ATPase, and BAs → cGMP → V‐ATPase. 5‐HT contents, Na + ‐K + ‐ATPase, and HCO3 − ‐ATPase activities in the starvation group were ultimately higher than those in the bilateral eyestalk ablation group, while the cyclic adenosine monophosphate (cAMP) contents increased slightly. Study results suggested that under the situation of bilateral eyestalk ablation, the shrimp could also use feed or its metabolites to increase 5‐HT or cAMP contents to regulate the Na + ‐K + ‐ATPase and HCO3 − ‐ATPase activities in gills.